Biosynthesis and role of 3-methylbutanal in cheese by lactic acid bacteria: Major metabolic pathways, enzymes involved, and strategies for control. Issue 2 (22nd January 2017) - Afzal, Muhammad Inam; Ariceaga, Citlalli Celeste González; Boulahya, Kenza-Amel; Jacquot, Muriel; Delaunay, Stéphane; Cailliez-Grimal, Catherine
ABSTRACT: Branched chain aldehyde, 3-methylbutanal is associated as a key flavor compound with many hard and semi-hard cheese varieties. The presence and impact of this flavor compound in bread, meat, and certain beverages has been recently documented, however its presence and consequences regarding cheese flavor were not clearly reported. This paper gives an overview of the role of 3-methylbutanal in cheese, along with the major metabolic pathways and key enzymes leading to its formation. Moreover, different strategies are highlighted for the control of this particular flavor compound in specific cheese types.